Effect of Mn content on structural, optical, opto-thermal and electrical properties of ZnO:Mn sprayed thin films compounds - YUMAK YAHŞİ, AYŞE (ELSEVIER SCIENCE SA, 2015)
Manganese-doped zinc oxide thin films (ZnO:Mn) at different percentages (0-3%) were deposited on glass substrates using a chemical spray technique. The effects of manganese element content on structural, optical, opto-thermal and electrical conductivity of ZnO:Mn thin films were investigated by means of X-ray diffraction, optical measurement, Photoluminescence spectroscopy and impedance spectroscopy. XRD analysis revealed that all films consist of single phase ZnO and were well crystallized in wurtzite phase with the crystallites preferentially oriented towards (002) direction parallel to c-axis. Doping manganese resulted in a slight decrease in the optical band gap energy of the films and a noticeably change in optical constants. The UV peak positions for ZnO:Mn samples slightly red shift to the longer wavelength in comparison with the pure ZnO which can be attributed to the change in the acceptor level induced by the substitutional Mn2+ and the band-gap narrowing of ZnO with the Mn dopant. We have performed original AC and DC conductivity studies inspired from Jonscher and small polaron models. These studies helped establishing significant correlation between temperature and activation energy and Mn content. From the spectroscopy impedance analysis we investigated the frequency relaxation phenomenon and the circuit equivalent circuit of such thin films. Finally, all results have been discussed, as an objective of the actual work, in terms of the manganese doping concentration. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Thin films; Mn-doped ZnO; Structure; Optical constants; Urbach tailing; Impedance spectroscopy; POLYNOMIALS EXPANSION SCHEME; BOUBAKER POLYNOMIALS; DOPED ZNO; SPATIAL EVOLUTION; KEYHOLE MODEL; GAS SENSOR; FERROMAGNETISM; SEMICONDUCTORS; CONDUCTIVITY; TEMPERATURE